A model of giant magnetostrictive actuator used in automobile engine fuel injection system. (1st January 2013) - Wang, Wenguo; Han, Hui; Han, Lu; Zhang, Yi
Developing a new type of automobile engine fuel injection system with a smart actuator instead of traditional serve valve controlling is the key source for the engine's fuel-saving and emission reduction. It is critical to solve the environmental protection and energy conservation issues of automobile industry. In this paper, a giant magnetostrictive injector with a giant magnetostrictive actuator is introduced. Working principles of giant magnetostrictive injector used in automobile and giant magnetostrictive actuator are elaborated. According to the actual working situation of giant magnetostrictive actuator in the automobile injector, an output displacement model is established on the basis of Preisach hysteresis theory. Experimental results show that, the agreement degree of output displacement's calculated value and measured value is good. The model provides a very accurate representation for displacement of the giant magnetostrictive actuator used in automobile injector in both the amplitude and frequency of the measured response. The achievements will open up a new way for the application and popularisation of giant magnetostrictive automobile engine injection system. It has an important significance to promote the automobile emission to meet standards.